Occurrnce of the neartic Phyllonorycter robiniellus (Clemens) (Lepidoptera Gracillariidae) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The occurrence of the neartic Phyllonorycter robiniellus (Clemens) (Lepidoptera Gracillariidae), leaf miner of Robinia pseudoacacia L., in Italy is pointed out in the present note.A morphological description and information on biology of the insect are also provided.
Keywords: Phyllonorycter robiniellus; black locust; Italy